A TRANSITION OF THE DRINKING WATER PROVISION IN INDONESIA - Sugiyono, - (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2012)
The result of this process are four alternative strategies. Finally the most reasonable and appropriate strategy is discussed in the end of this part.